Databook of antiblocking, release and slip additives - Wypych, Anna (ChemTec Publishing, 2021)
"Databook of Antiblocking, Release, and Slip Additives contains data on ~300 of the most essential additives. It contains 145 data fields to accommodate a variety of data available in source publications. The additive databook is divided into five sections: General information, Physical properties, Health and safety, Ecological properties, and Use & Performance and contains any of the listed below data if they are available for a compound."--